The Language Attitude of the Tanjungpinang City Towards the Indonesian Language (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The Tanjung City Community has distinctive characteristics in terms of language. Cities that are located between two countries, namely Singapore and Malaysia, have a big influence in terms of acting speech in their daily lives. This study aims to describe the form of language attitude, which consists of language, language pride, and awareness of language norms. This study uses a sociolinguistic approach and a qualitative approach. The data of this study is a piece of speech from Tanjungpinang city community in the realm of education in daily communication in the classroom during teaching and learning activities. The observation point, namely Public High School 1 Bintan Timur, Public High School Tanjungpinang 1, and Public High School Tanjungpinang 2. This research produces the following findings. First, the manifestation of language loyalty in the realm of education in-class language loyalty that is realized through fragments of conversation that occur, language pride, and awareness of the existence of norms that are analyzed based on pragmatic rules and diction to produce findings that violate good and correct language rules.